2022
DOI: 10.1186/s12978-022-01520-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of induced abortion: results of a facility-based cross-sectional survey of parturient women living with HIV in South Africa

Abstract: Background There is a paucity of studies examining the prevalence and correlates of induced abortion among women living with HIV. Our study fills this gap by examining the prevalence and correlates of induced abortion among parturient women living with HIV in Eastern Cape, South Africa. Methods We analysed cross-sectional survey data of the East London Prospective Cohort Study, which took place between September 2015 and May 2016 in three large mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Unsafe abortion poses a serious risk to adolescents, especially compared to much older women. Yet, a study conducted in Ghana indicated that adolescents face barriers such as stigma when accessing the country's abortion services, where healthcare providers serve as gatekeepers to abortion services [21]. In the context of our study, no abortion-on-demand services are permitted or offered.…”
Section: Discussionmentioning
confidence: 94%
“…Unsafe abortion poses a serious risk to adolescents, especially compared to much older women. Yet, a study conducted in Ghana indicated that adolescents face barriers such as stigma when accessing the country's abortion services, where healthcare providers serve as gatekeepers to abortion services [21]. In the context of our study, no abortion-on-demand services are permitted or offered.…”
Section: Discussionmentioning
confidence: 94%
“…Women who used drugs or alcohol were significantly more likely to have an induced abortion (AOR = 2.72, 95% CI: 1.38–5.34) ( Fig 9 ). The four included studies [ 24 , 31 , 38 , 55 ] showed moderate heterogeneity, and Egger’s tests for the small study effect revealed a significant small study effect and the presence of publication bias (p = 0.029). As a result, a trim-and-fill analysis for substance usage was carried out in order to lessen and correct the research’s apparent publication bias.…”
Section: Resultsmentioning
confidence: 99%
“…For most pregnant women, the choice of induced abortion will undoubtedly cause some harm to the body. According to some studies, induced abortion may cause genital infection, depression anxiety, and other situations, and it can also cause diseases such as breast cancer [18][19][20]39] . Our study utilized UK biobank recorded information on induced abortion in British women as well as bipolar disorder and major depression, After the results of the multivariate regression analysis based on the inverse probability weighting and the propensity score matching, We found that induced abortion was an independent risk factor for bipolar affective disorder and major depression.…”
Section: Page 9/16mentioning
confidence: 99%